Open Data and the Knowledge Society - Wessels, Bridgette; Finn, Rachel; Wadhwa, Kush (Amsterdam University Press, 2017)
While there is a lot of talk about how we now live in a knowledge society, the reality has been less impressive: We have yet to truly transition to a knowledge society-in part, this book argues, because discussion mostly focuses on a knowledge economy and information society rather than on ways to mobilise to create an actual knowledge society. That all may change, however, with the rise of open data and big data. This book considers the role of the open data movement in fostering transformation, showing that at the heart of any successful mobilisation will be an emerging open data ecosystem and new ways for societal actors to effectively produce and use data.